1973
DOI: 10.1159/000301713
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Pregnenolone <i>Δ</i><sup>5</sup>–3β-Hydroxysteroid Dehydrogenase-<i>Δ</i><sup>5-</sup><sup>4</sup> Isomerase Systems of Human Placenta and Corpus Luteum of Pregnancy

Abstract: The inhibition of the pregnenolone Δ5–3Β-hydroxysteroid dehydrogenase-Δ5-4 isomerase systems in microsomes of human placenta or corpus luteum of pregnancy has been investigated using three steroidal substances: 2Α-cyano- 4,4,17Β-trimethylandrost-5-en-17Α-ol-3-one (cyanoketone), 2- hydroxymethylene, 17Α-methyl-5Α-androstan-17Β-ol-3-one (oxymetholone), and estradiol 17Β. The inhibition is of the competitive type with the synthetic steroids. The apparent Ki’s are approximately 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Estrogen has been shown to decrease luteal 3␤-hydroxysteroid dehydrogenase activity in vitro (50,51), providing a mechanism by which estrogens may further reduce luteal progesterone production in vivo. In the nonfertile menstrual cycle, decreasing LH pulse frequency (49) creates lengthening periods of relative progesterone deprivation, which may result in increased luteal ER␤ levels and enhanced luteal sensitivity to locally produced estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been shown to decrease luteal 3␤-hydroxysteroid dehydrogenase activity in vitro (50,51), providing a mechanism by which estrogens may further reduce luteal progesterone production in vivo. In the nonfertile menstrual cycle, decreasing LH pulse frequency (49) creates lengthening periods of relative progesterone deprivation, which may result in increased luteal ER␤ levels and enhanced luteal sensitivity to locally produced estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…389,393 The self-destruct hypothesis was supported further by the observation that the addition of estradiol to isolated macaque luteal cells inhibited both basal and gonadotropin-stimulated progesterone production. 394,395 This attractive hypothesis, which would account for the observations that luteal regression does not appear to be due to a reduction in LH secretion, was questioned by subsequent observations in which sensitive bioassays were used to measure serum LH concentrations during estradiol-induced luteolysis. These studies revealed that estradiol-induced luteal regression was preceded by slight, but significant, declines in plasma LH concentrations during exposure to exogenous estradiol.…”
Section: Estradiol As a Luteolysinmentioning
confidence: 99%
“…Another possibility might be that the in vitro inhibition by estradiol proceeds by a completely different mechanism than that in the in vivo effect. The former action could simply occur by direct inhibition of the A 5 -3/Miydroxysteroid dehydrogenase, A 5 ' 4 -isomerase system (13). Further studies will be necessary to resolve this difference.…”
Section: Discussionmentioning
confidence: 99%